CYBER FORENSICS-A REVIEW (International Journal of Engineering and Computer Science, 2013)
Network crimes are the most unpredictable calamity on the cyber world. Unauthorized access,hacking, spreading of viruses, smashing computer networks on very large scale, the brutal weapons like emailbombing, logic bombs resulting into the disrupt behavior of computer networks are very few incidencesof recent days. Security of information systems against them is the protection of availability, confidentialityand integrity. The relative priority and significance of availability, confidentiality and integrity varyaccording to the information system. The legislation should address computers and computer material asunique objects and cover all computer-related aspects in the categories of crimes by means of computersand crimes against computers. The Union Government of India has started now to establish special cybercrime units for controlling such crimes.